Mimicking Rosacea? Jessner’s Lymphocytic Infiltration of the Skin: A Case Report - Li L; Wang Y; Gu H (Clinical, Cosmetic and Investigational Dermatology, 2024)
Lingjia Li,1 Yulan Wang,2 Hua Gu2 1Department of Dermatology, Jiangnan University Medical Center, Jiangnan University, Wuxi, People’s Republic of China; 2Department of Dermatology, The First Affiliated Hospital of Kunming Medical University Kunming, Kunming, People’s Republic of ChinaCorrespondence: Hua Gu, Department of Dermatology, The first Affiliated Hospital of Kunming Medical University Kunming, Kunming, People’s Republic of China, Tel +86-18762675765, Email guhua1978@sina.comAbstract: We report a case of rash in a 35-year-old female presenting with erythematous papules and infiltrative plaques on the nose and upper jaw resembling rosacea. The patient had been experiencing these symptoms for one year. A pathological biopsy revealed an inflammatory infiltrate consisting of dense perivascular lymphocytes surrounding hair follicles and sweat glands in the dermis. Immunohistochemistry demonstrated a predominance of CD4+ T cells compared to CD8+ T cells. Based on the clinical manifestations, histopathology, and immunohistochemistry, the patient was diagnosed with Jessner’s Lymphocytic infiltration of the skin (JLIS). The patient was treated with oral Minocycline, 100mg twice daily. After 4 weeks, the dosage was reduced by half and the treatment continued for 2 months, resulting in complete resolution of the rash. The clinical presentation resembled rosacea, and this particular manifestation of JLIS has not been previously reported. Treatment with minocycline yielded satisfactory efficacy, and no recurrence has been observed for 5 year.Keywords: lymphocytic infiltration, skin, rosacea, minocycline